Water soluble Eu(III) complexes of macrocyclic triamide ligands: Structure, stability, luminescence and redox properties - Pujales Paradela, Rosa; et al. (Inorganica Chimica Acta, 2019)
Two macrocyclic triamide octadentate chelator scaffolds L-1 and L-2 were synthesized, characterized by several spectroscopic techniques, and their pK(a) values were determined by potentiometric titration. Using these ligands, two water soluble paramagnetic Eu(III) complexes, [EuL1(OH2)](NO3)(3)center dot H2O (EuL1) and [EuL2(OH2)](NO3)(3)center dot H2O (EuL2) were synthesized and characterized in the solid state and in solution. Single crystal X ray diffraction measurement of [EuL1(OH2)](NO3)(3)center dot H2O (EuL1) reveals octadentate binding of the ligand to Eu(III) and ninth coordination being completed by an oxygen atom of a solvent molecule (H2O). X-ray diffraction data of [EuL2(OH2)](NO3)(3)center dot H2O (EuL2) were severely disordered and hence its chloride analogue [EuL2(DMF)]Cl-3 center dot H2OMeOH (EuL2-Cl) was synthesized and characterized using single-crystal X-ray diffraction measurements. The crystal data of [EuL2(DMF)](Cl)(3)center dot H2OMeOH (EuL2-Cl) reveal octadentate binding of the ligand to Eu(III), with the ninth coordination being completed by an oxygen atom of a solvent molecule (DMF). Luminescence measurements confirm the presence of a water molecule coordinated to Eu(III) in aqueous solution. The stability of the Eu(III) complexes was investigated using spectrophotometric molar ratio method. Cyclic voltammetry studies obtained from aqueous solutions of the Eu(III) complexes show reversible one electron reduction processes at the glassy carbon electrode with E-1/2 = -0.799 V and -0.777 V (versus Ag/AgCl) for the complexes of L-1 and L-2.
Keywords: Eu(III) macrocyclic complexes; X-Ray; Luminescence; Redox properties; pKa & stability constant; DFT calculation